2014
DOI: 10.1111/jopy.12096
|View full text |Cite
|
Sign up to set email alerts
|

Social Exclusion Predicts Impaired Self-Regulation: A 2-Year Longitudinal Panel Study Including the Transition from Preschool to School

Abstract: The need‐to‐belong theory stipulates that social exclusion (i.e., being rejected by peers) impairs the ability to self‐regulate, and experimental studies with adults support this contention, at least on a short‐term basis. Few studies have investigated whether social exclusion affects the development of self‐regulation of children in a more enduring manner. By using data from a community sample of 762 children, we investigated reciprocal relations between social exclusion and self‐regulation from age 4 to age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 61 publications
(83 reference statements)
8
57
0
5
Order By: Relevance
“…Similarly, a recent review highlighted the bidirectional relations between adolescents’ self-regulation and peer relationships such that better self-regulation contributed to better peer relations and vice-versa (Farley & Kim-Spoon, 2014). Also in parallel support of the proposed reciprocal relation between EF and PP, Stenseng and colleagues (2014) found that social exclusion of peers was linked with impaired self-regulation in the transition from preschool to elementary school and vice versa such that social exclusion was associated with impaired development of self-regulation 2 years later and poor self-regulation was associated with greater social exclusion 2 years later. However, this study is limited as it considered only two time points at age 4 and age 6 and their self-regulation measure assessed pathological deficiencies in regulation and temperamental regulation capacity, but did not consider cognitive regulation related specifically to EF.…”
Section: The Reciprocal Link Between Peer Problems and Executive Funcmentioning
confidence: 55%
“…Similarly, a recent review highlighted the bidirectional relations between adolescents’ self-regulation and peer relationships such that better self-regulation contributed to better peer relations and vice-versa (Farley & Kim-Spoon, 2014). Also in parallel support of the proposed reciprocal relation between EF and PP, Stenseng and colleagues (2014) found that social exclusion of peers was linked with impaired self-regulation in the transition from preschool to elementary school and vice versa such that social exclusion was associated with impaired development of self-regulation 2 years later and poor self-regulation was associated with greater social exclusion 2 years later. However, this study is limited as it considered only two time points at age 4 and age 6 and their self-regulation measure assessed pathological deficiencies in regulation and temperamental regulation capacity, but did not consider cognitive regulation related specifically to EF.…”
Section: The Reciprocal Link Between Peer Problems and Executive Funcmentioning
confidence: 55%
“…Moreover, the underlying mechanism that illuminates how social exclusion influences consumers' food self‐regulation is still unknown. Importantly, a considerable body of research has already demonstrated that social exclusion undermines self‐regulation (e.g., Baumeister et al, ; Oaten, Williams, Jones, & Zadro, ; Stenseng et al, ). For example, Baumeister et al () have found that excluded participants have more difficulty in making themselves consume a healthy but bad‐tasting beverage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the underlying mechanism that illuminates how social exclusion influences consumers' food self-regulation is still unknown. Importantly, a considerable body of research has already demonstrated that social exclusion undermines self-regulation (e.g., Baumeister et al, 2005;Oaten, Williams, Jones, & Zadro, 2008;Stenseng et al, 2015).…”
Section: The Impact Of Social Exclusion On Food Selfregulationmentioning
confidence: 99%
See 2 more Smart Citations